Algal cultivation in urban wastewater: an efficient way to reduce pharmaceutical pollutants - Gentili, Francesco G.; Fick, Jerker (Journal of applied phycology, 2017)
The purpose of this study was to investigate whether pharmaceutical pollutants in urban wastewater can be reduced during algal cultivation. A mixed population of wild freshwater green algal species was grown on urban wastewater influent in a 650 L photobioreactor under natural light and with the addition of flue gases. Removal efficiencies were very high (>90 %), moderate (50–90 %), low (10–50 %), and very low or non-quantifiable (<10 %) for 9, 14, 11, and 18 pharmaceuticals, respectively, over a 7-day period. High reduction was found in the following pharmaceuticals: the beta-blockers atenolol, bispropol, and metoprolol; the antibiotic clarithromycine; the antidepressant bupropion; the muscle relaxant atracurium; hypertension drugs diltiazem and terbutaline used to relive the symptoms of asthma. Regression analysis did not detect any relationship between the reduction in pharmaceutical contents and light intensity reaching the water surface of the algal culture. However, the reduction was positively correlated with light intensity inside the culture and stronger when data collected during the night were excluded. Algae cultivation can remove partially or totally pharmaceutical pollutants from urban wastewater, and this opens up new possibilities for treating urban wastewater.